The Application of Bead-Stringing Play in Stimulasting Fine Motor Skills of Children Aged 4-5 Years at TK Al-Kautsat Bontang - Syarifah Zafira Zain; Fitri Anjarwati; Wilda Isna Kartika (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
This study aims to describe the implementation of bead-stringing play activities as a solution to stimulate the fine motor skills of children aged 4–5 years at TK Al-Kautsar Bontang and to identify the teacher’s role in providing stimulation that enables children to gradually develop their fine motor abilities according to their individual capacities. The research employed a descriptive qualitative method with 10 Class A children and 1 teacher as the subjects. Data were collected through observation, interviews, and documentation. The bead-stringing activities were carried out through five stages: introduction to the activity, texture introduction, free bead-stringing, structured ABAB patterns, and structured AABB patterns. The results of the study show that providing different stimuli at each process effectively encouraged the development of eye–hand coordination, finger control, accuracy, concentration, and children’s independence. The activities, conducted regularly two to three times a week with teacher assistance, proved effective in stimulating the fine motor skills of children aged 4–5 years. Bead-stringing can be used by teachers as a gradual strategy to stimulate children’s fine motor development, especially for children who still need practice with focus and hand flexibility. The teacher plays an important role by providing demonstrations, guidance, and variations of materials, making the activity more engaging and enjoyable. The teacher’s sensitivity in observing each child’s abilities also enables the gradual adjustment of stimuli.